2021
DOI: 10.2196/33049
|View full text |Cite
|
Sign up to set email alerts
|

Differential Biases and Variabilities of Deep Learning–Based Artificial Intelligence and Human Experts in Clinical Diagnosis: Retrospective Cohort and Survey Study

Abstract: Background Deep learning (DL)–based artificial intelligence may have different diagnostic characteristics than human experts in medical diagnosis. As a data-driven knowledge system, heterogeneous population incidence in the clinical world is considered to cause more bias to DL than clinicians. Conversely, by experiencing limited numbers of cases, human experts may exhibit large interindividual variability. Thus, understanding how the 2 groups classify given data differently is an essential step for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Significant performance differences were found when non-otolaryngologists were asked to differentiate between acute otitis media (AOM), otitis media with effusion (OME), or retracted TMs 8 . These findings are consistent with recent studies that demonstrate that diagnostic accuracy is reduced when non-experts must differentiate between multiple ear disease sub-types 6 , 11 . Otolaryngologists significantly outperformed non-otolaryngologists to identify ear disease sub-types and important pathological characteristics (e.g.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Significant performance differences were found when non-otolaryngologists were asked to differentiate between acute otitis media (AOM), otitis media with effusion (OME), or retracted TMs 8 . These findings are consistent with recent studies that demonstrate that diagnostic accuracy is reduced when non-experts must differentiate between multiple ear disease sub-types 6 , 11 . Otolaryngologists significantly outperformed non-otolaryngologists to identify ear disease sub-types and important pathological characteristics (e.g.…”
Section: Introductionsupporting
confidence: 92%
“…Otoscopy is performed routinely by multiple healthcare workers including medical students, nurses, general practitioners, emergency medicine physicians, paediatricians, audiologists, and otolaryngologists. However, the ability to accurately interpret otoscopic findings varies by user experience 6 10 . Pichichero et al (2005) demonstrated differences between general practitioners, paediatricians, and otolaryngologists to recognise tympanic membrane (TM) abnormalities 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have applied AI to otological imaging in various clinical contexts (Supplemental File 3, available online). These studies combined AI with otoscopy, [22][23][24][25][26]31,32,38,48,52,57,68,[74][75][76]79,81,84,85,93,95 computed tomography (CT), 30,36,41,42,50,62,63,70,71,88 and magnetic resonance imaging (MRI). 43,73,78 Most studies have focused on the image-based otoscopic diagnosis and automated segmentation of temporal bone CT for classifying normal and abnormal mastoid air cells.…”
Section: Application Of Ai In Otologymentioning
confidence: 99%
“…The differences between training AI models and human experts and their distinct strengths and limitations in the diagnostic process lead to AI-HI cooperation. For instance, AI models have shown statistical bias towards prevalent diseases 13 , 14 , yet maintain remarkable consistency 15 . Conversely, human experts, while not as biased towards prevalent conditions, exhibit significant inter-rater variability 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%